Ranking strategic and operative goals for sustainable development of Pohorje, Slovenia - Grošelj, Petra (Acta silvae et ligni, 2013)
The combination of participatory process and multi-criteria decision methods have proven to be effective in supporting forest management decisions, since it offers inclusion of different opinions, views, and preferences of the problem. Our study is based on the results of the NATREG project, which deals with management of Pohorje, a mountain area in Slovenia. The results define six strategic goals and appertaining operative goals, which are the outcomes of workshops with different stakeholders. The aim of our study is ranking the strategic goals according to their contribution in the implementation of the "Pohorje 2030" vision and of the operative goals according to the appertaining strategic goals. Analytic hierarchy process is applied for comparisons of goals. Geometric mean method is employed for aggregating individual judgments into group judgment. The results show that all strategic goals are important, although most attention should be devoted to the goals "Preserved cultural heritage and local tradition" and "Environmental and consumer friendly usage of natural resources".
Keywords: analitični hierarhični proces; skupinsko odločanje; sustainable development; trajnostni razvoj; naravni viri; gospodarjenje z gozdovi